Development and validation of a mathematical equation to estimate glomerular filtration rate in cirrhosis: The royal free hospital cirrhosis glomerular filtration rate. Issue 2 (29th November 2016) - Kalafateli, Maria; Wickham, Fred; Burniston, Maria; Cholongitas, Evangelos; Theocharidou, Eleni; Garcovich, Matteo; O'Beirne, James; Westbrook, Rachel; Leandro, Gioacchino; Burroughs, Andrew K.; Tsochatzis, Emmanuel A.
Abstract : Current expressions based on serum creatinine concentration overestimate kidney function in cirrhosis, leading to significant differences between "true" and calculated glomerular filtration rate (GFR). We compared the performance of the four‐variable and six‐variable Modification of Diet in Renal Disease and chronic kidney disease epidemiology with "true, " or measured, GFR (mGFR) and the impact of this difference on Model for End‐Stage Liver Disease (MELD) calculation. We subsequently developed and validated a GFR equation specifically for cirrhosis and compared the performance of the new derived formula with existing GFR formulae. We included 469 consecutive patients who had a transplant assessment between 2011 and 2014. mGFR was measured using plasma isotope clearance according to a technique validated in patients with ascites. A corrected creatinine was derived from the mGFR after application of the Modification of Diet in Renal Disease formula. Subsequently, a corrected MELD was calculated and compared with the conventionally calculated MELD. Stepwise multiple linear regression was used to derive a GFR equation. This was compared with the mGFR in independent external and internal validation sets of 82 and 174 patients with cirrhosis, respectively. A difference >20 mL/minute/1.73 m 2 between existing formulae and mGFR was observed in 226 (48.2%) patients. The corrected MELD score was ≥3 points higher in 177 (37.7%) patients. The predicted equation ( r 2 = 74.6%) was GFR = 45.9 × (creatinine –0·836 ) × (urea –0·229 ) × (international normalized ratio –0·113 ) × (age −0.129 [Corrected November 29, 2016: originally written as "age‐129."]) × (sodium 0·972 ) × 0.809 (if female) × 0.92 (if moderate/severe ascites). An online calculator is available at http://rfh-cirrhosis-gfr.ucl.ac.uk . The model was a good fit and showed the greatest accuracy compared to that of existing formulae. Conclusion : We developed and validated a new accurate model for GFR assessment in cirrhosis, the Royal Free Hospital cirrhosis GFR, using readily available variables; this remains to be tested and incorporated in prognostic scores in patients with cirrhosis. (Hepatology 2017;65:582‐591).